Seismic performance evaluation of full-scale mass timber structures: comparative insights from tall and mid-rise shake table test programs - Mishra, Prashanna, author; van de Lindt, John W., advisor; Jia, Gaofeng, committee member; Shields, Martin, committee member (Colorado State University. Libraries, 2025)
This thesis presents an overview of the design, construction, and testing of full-scale mass timber building specimens as part of two major multi-university projects - the NHERI TallWood and NHERI Converging Design research projects. These projects both focused on ensuring resilience for tall and mid-rise wood buildings in high seismic regions, with one focusing on structural and non-structural design for resilience and the other adding considerations for sustainability. Over the past decade, advances in materials, manufacturing, components, and building systems have enabled taller mass timber construction. However, most existing tall wood buildings still rely on concrete cores or steel bracing for lateral force-resisting systems due to limited code-approved mass timber options and industry reliance on traditional systems. The NHERI TallWood test building incorporated a post-tensioned mass timber rocking wall system, a low-damage gravity framing system, and drift-compatible non-structural components. Standing 34.4 m (113 ft) tall with a uniform 84 m² (900 ft²) floor plan, it was constructed and tested on the NHERI@UCSD outdoor shake table in Miramar, California. The system was designed to meet standard office loading criteria, with a 2-hour fire rating, and featured a range of floor systems including nail-laminated timber (NLT), dowel-laminated timber (DLT), and 5-ply cross-laminated timber (CLT) panels. Connections at the column bases at ground level were designed to allow free rotation up to 5% drift, ensuring damage-free performance during seismic events. The NHERI Converging Design structure, constructed by deconstructing the top four floors of the TallWood building, was 20.4 m (67 ft) tall and used a similar post-tensioned rocking wall system but with a modified lateral force-resisting design approach. It was also tested on the NHERI@UCSD shake table, providing valuable comparative data on the seismic performance of both designs since they had the exact same footprint and very similar relative lateral force resistance to weight. This research represents the first time post-tensioned rocking walls have been physically tested at full scale in such tall buildings. The results from these shake table tests, representing the tallest mass timber buildings ever tested, provided critical data for validating seismic design methodologies and supporting the adoption of resilient mass timber lateral systems in tall and mid-rise wood buildings in seismic regions.
Keywords: post-tensioned rocking walls; seismic performance evaluation; mass timber structures; shake table testing; resilient structural design